Position Control of a Ball & Beam Experimental Setup Based on Sliding Mode Controller - Kaan CAN; Abdullah Başçi (International Journal of Applied Methods in Electronics and Computers, 2017)
In this paper, a sliding mode control (SMC) method is introduced to design a control methodology for the ball and beam experimental setup (BBS) that consists of a servo motor, beam and ball. The proposed control method is realized in two cascaded control structures such that primary and secondary, respectively. In the primary part, called outer loop, the position of the ball is controlled by changing the angle of the beam. In the secondary part, called inner loop, the needed voltage is generated to determine appropriate position angle of the servo motor to adjust the position of the beam. Furthermore, a well-tuned conventional PI controller is also applied to the system to indicate the priority and effectiveness of the SMC. The results obtained in real-time show that the SMC is better than the PI controller in the aspect of reference tracking, fast response to the changes and accuracy as well.